Native Subterranean Termites: Reticulitermes flavipes (Kollar), Reticulitermes virginicus (Banks), Reticulitermes hageni Banks (Insecta: Isoptera: Rhinotermitidae) - Nan-Yao Su; Rudolf H. Scheffrahn; Brian Cabrera (EDIS)
Most pest species of subterranean termites in North America belong to the endemic genus Reticulitermes. Reticulitermes species are found in every state in the continental United States except Alaska, but are most common in the warm and humid southeastern region. The eastern subterranean termite, R. flavipes is the most widely distributed and is found in the entire eastern region of North America as far north as Ontario, Canada, and south to Key Largo, Florida. Its counterpart, the western subterranean termite, R. hesperus Banks, is found along the entire Pacific Coast ranging from southern California to British Columbia. Reticulitermes tibialis occurs in the inter-mountain region of the West. In addition to R. flavipes, two other Reticulitermes occur in Florida, R. virginicus, and R. hageni. This document is EENY-212, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2001.